A tumor acidity activatable and Ca2+-assisted immuno-nanoagent enhances breast cancer therapy and suppresses cancer recurrence. Issue 28 (6th July 2020) - Li, Yanhua; Gong, Shaohua; Pan, Wei; Chen, Yuanyuan; Liu, Bo; Li, Na; Tang, Bo
Abstract : A tumor acidity activatable and Ca 2+ -assisted immuno-nanoagent was developed to enhance cancer immunotherapy and protect mice from tumor recurrence after surgery. Abstract : Breast cancer recurrence is the greatest contributor to patient death. As the immune system has a long-term immune memory effect, immunotherapy has great potential for preventing cancer recurrence. However, cancer immunotherapy is often limited due to T cell activation being blocked by insufficient tumor immunogenicity and the complex immunosuppressive tumor microenvironment. Here we show a tumor acidity activatable and Ca 2+ -assisted immuno-nanoagent to synergistically promote T cell activation and enhance cancer immunotherapy. When the immuno-nanoagent reaches the acidic tumor microenvironment, the CaCO3 matrix disintegrates to release immune stimulants (CpG ODNs and IDOi) and Ca 2+ . CpG ODNs are responsible for triggering dendritic cell maturation to increase the immunogenicity for activation of T cells. And IDOi can inhibit the oxidative catabolism of tryptophan to kynurenine for preventing T-cell anergy and apoptosis. Due to the complexity of the immunosuppressive microenvironment, it is difficult to restore T cell activation by inhibiting only one pathway. Fortunately, the released Ca 2+ can promote the activation and proliferation of T cells with the support of the immune stimulants. In vivo experiments demonstrate that our Ca 2+ -assisted immuno-nanoagent can significantly suppress tumor progression and protect mice from tumor rechallenge due to the long-term memory effect. This immunotherapeutic strategy may provide more possibilities for clinical applications such as treating cancer and preventing relapse.